Interplay Between Traditional and Scientific Knowledge: Phytoconstituents and Their Roles in Lung and Colorectal Cancer Signaling Pathways - Ilma Imtiaz; Janet Schloss; Andrea Bugarcic (Biomolecules)
Natural plant products have been used for cancer treatment since ancient times and continue to play a vital role in modern anticancer drug development. However, only a small fraction of identified medicinal plants has been thoroughly investigated, particularly for their effects on cellular pathways in lung and colorectal cancers, two under-researched cancers with poor prognostic outcomes (lung cancers). This review focuses on the lung and colorectal cancer signaling pathways modulated by bioactive compounds from eleven traditional medicinal plants: Curcuma longa, Astragalus membranaceus, Glycyrrhiza glabra, Althaea officinalis, Echinacea purpurea, Sanguinaria canadensis, Codonopsis pilosula, Hydrastis canadensis, Lobelia inflata, Scutellaria baicalensis, and Zingiber officinale. These plants were selected based on their documented use in traditional medicine and modern clinical practice. Selection criteria involved cross-referencing herbs identified in a scoping review of traditional cancer treatments and findings from an international survey on herbal medicine currently used for lung and colorectal cancer management by our research group and the availability of existing literature on their anticancer properties. The review identifies several isolated phytoconstituents from these plants that exhibit anticancer properties by modulating key signaling pathways such as PI3K/Akt/mTOR, RAS/RAF/MAPK, Wnt/β-catenin, and TGF-β in vitro. Notable constituents include sanguinarine, berberine, hydrastine, lobeline, curcumin, gingerol, shogaol, caffeic acid, echinacoside, cichoric acid, glycyrrhizin, 18-β-glycyrrhetinic acid, astragaloside IV, lobetyolin, licochalcone A, baicalein, baicalin, wogonin, and glycyrol. Curcumin and baicalin show preclinical effectiveness but face bioavailability challenges, which may be overcome by combining them with piperine or using oral extracts to enhance gut microbiome conversion, integrating traditional knowledge with modern strategies for improved outcomes. Furthermore, herbal extracts from Echinacea, Glycyrrhiza, and Codonopsis, identified in traditional knowledge, are currently in clinical trials. Notably, curcumin and baicalin also modulate miRNA pathways, highlighting a promising intersection of modern science and traditional medicine. Thus, the development of anticancer therapeutics continues to benefit from the synergy of traditional knowledge, scientific innovation, and technological advancements.